Epidemiology of acinetobacter sepsis in infants admitted to a neonatal unit - Thomas, Reenu (My University, 2016)
Background: Acinetobacter baumannii (A. baumannii) is emerging as one of the pathogens causing sepsis in neonates. Prevalence, antibiotic susceptibilities and case-fatality rate (CFR) of A. baumannii in the neonatal units are not well known. Objective: To determine the prevalence, antibiotic susceptibility patterns and CFR of A. baumannii infection in neonates. Methods: Medical records of neonates admitted to Chris Hani Baragwanath Academic Hospital from 1st October 2007 to 31st October 2011 with a positive blood or cerebrospinal fluid culture due to A. baumannii were reviewed for demographic characteristics, clinical presentation, laboratory findings, antibiotic susceptibility and outcome. Results: There were 399 isolates of A. baumannii, with a prevalence of 4.3/1000 live births or 2/ 1000 patient-days, and accounting for 13% of all bacterial and fungal isolates. Antimicrobial susceptibility results were available for 379 isolates and only 155 medical records could be retrieved for analysis. The mean gestational age and birth weight of infected neonates was 30 weeks and 1400 grams respectively. Thirty seven (24%) were isolated from neonates with early onset sepsis and 118 (76%) from those with late onset sepsis. Sixty four percent of isolates were susceptible to Cephalosporins, 21% to Aminoglycosides and 17% were multi-drug resistant (MDR) isolates. The CFR was 32%. Factors associated with mortality were presence of a central venous catheter prior to onset of sepsis (49% vs 31%, p=0.03); need for ventilatory support (62% vs 36%, p=0.005) and inotropic support (57% vs 17%, p<0.001). Conclusions: A. baumannii is a common pathogen causing sepsis in neonates, with 17% of them being MDR. It is associated with high CFR. These findings highlight the need for strict enforcement of infection control and antibiotic stewardship practices.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master in Medicine. Johannesburg 2015
Keywords: Acinetobacter; Infant; Intensive Care Units, Neonatal; Sepsis